Public Safety Awareness of the Covid-19 Pandemic Through Pamphlet Media in Semangat Bakti Village, Barito Kuala Regency - Noor Baiti (UMBanjarmasin, 2022)
Corona virus is a global outbreak The covid 19 pandemic is a very contagious outbreak. People should feel concerned about the outbreak that is hitting. Public awareness is the main key in preventing or breaking the chain of the spread of the covid 19 disease. There are many concepts carried out by the government in preventing Covid-19, one of which is through lockdown, social distancing or others. If people can discipline themselves and have awareness and high spirits it will never work. Therefore, it is necessary to socialize or provide education through the distribution of pamphlets about dangers other than hoax news, especially news about covid 19 in Semangat Bakti Village, Barito Kuala Regency